DIAGNOSTIC ACCURACY OF FAST SCAN IN PATIENT WITH BLUNT ABDOMINAL TRAUMA KEEPING CECT ABDOMEN AS GOLD STANDARD (Journal of Medical & Health Sciences Review, 2025)
Introduction: Blunt abdominal trauma (BAT) remains a significant cause of morbidity and mortality. FAST is a non-invasive ultrasound modality primarily employed to detect free intra-peritoneal fluid suggestive of heamoperitoneum. CECT abdomen is used in stable patients for its superior ability to delineate solid organ injuries, retroperitoneal involvement, and vascular compromise. This study evaluates the diagnostic accuracy of FAST compared to CECT in patients with blunt abdominal trauma, using CECT findings as the gold standard. Methodology: A cross-sectional study was conducted at CMH Muzaffarabad from September 19, 2023, to March 18, 2024, involving 140 patients with history of blunt abdominal trauma. Ultrasonography (FAST scan) was used initially for screening the trauma patients for the presence or absence of free intra-peritoneal fluid. CECT abdomen was performed to detect any free intra-peritoneal fluid and visceral injury which serve as a gold standard. Parameters assessed included sensitivity, specificity, PPV, NPV, and accuracy.Results: In a study with 140 patients, 85% were male and 15% were female, with a mean age of 29.0071 ±10.42 years. The types of trauma experienced were predominantly Road traffic accident (65.7%), History of Fall (28.5%), Assault (5.7%). The FAST scan results revealed that 40% of the patients had positive findings, while 60% had negative findings. In comparison, CECT findings were positive in 35% and negative in 65% of the cases.Conclusion: In conclusion, the FAST scan is a valuable tool in the rapid assessment of abdominal trauma. However, its diagnostic limitations, necessitate cautious interpretation. The integration of FAST with other diagnostic modalities, continued operator training, and possibly the adoption of advanced techniques may improve outcomes in trauma care.